Time perception is distorted during responses to medical emergencies - Eisen, Lewis A. (Medical hypotheses, 2009)
An accurate perception of time is critical for responders to cardiac arrests and other medical emergencies. Interventions such as medications or defibrillation are meant to be given at particular times. External chest compressions and bag-valve mask ventilations should be done at a particular rate. Accurate timing of the length of pulselessness may have implications for post-emergency management. Additionally, reported timing of pulselessness may alter clinicians’ perception of the patient’s chances for neurological recovery. Prior research indicates that stressful situations may impair subjects’ time perception. It is hypothesized that this is true for responders to medical emergencies. Although there are many competing factors, responders to medical emergencies most likely feel that time passes more slowly than it actually does. This could have important implications for patient management both during and after medical emergencies.